Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1523/jneurosci.20-01-00315.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Calcineurin by Growth Cone Calcium Waves Controls Neurite Extension

Abstract: Growth cones generate spontaneous transient elevations of intracellular Ca(2+) that regulate the rate of neurite outgrowth. Here we report that these Ca(2+) waves inhibit neurite extension via the Ca(2+)-dependent phosphatase calcineurin (CN) in Xenopus spinal neurons. Pharmacological blockers of CN (cyclosporin A and deltamethrin) and peptide inhibitors of CN [the Xenopus CN (xCN) autoinhibitory domain and African swine fever virus protein A238L] block the Ca(2+)-dependent reduction of neurite outgrowth in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 75 publications
1
102
0
Order By: Relevance
“…Changes in cytoskeletal organization and roles they may play in migration have been studied in cerebellar granule neurons (30,31). Calcium transients were proved to regulate growth cone motility through the Ca 2ϩ -dependent phosphatase calciueurin and the latter ultimately affects the growth cone actin cytoskeleton (32,33). Recently it was reported that Ca 2ϩ transients regulate the growth cone motility and guidance through activation of the protease calpain (29).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cytoskeletal organization and roles they may play in migration have been studied in cerebellar granule neurons (30,31). Calcium transients were proved to regulate growth cone motility through the Ca 2ϩ -dependent phosphatase calciueurin and the latter ultimately affects the growth cone actin cytoskeleton (32,33). Recently it was reported that Ca 2ϩ transients regulate the growth cone motility and guidance through activation of the protease calpain (29).…”
Section: Discussionmentioning
confidence: 99%
“…The relation between calcium transients and cAMP signaling may be different between the central domain of the growth cone and its filopodia [19]. Further, manipulating growth cone calcium waves is sufficient to affect neurite extension directly [65].…”
Section: Reviewmentioning
confidence: 99%
“…In particular, Ca 2+ transients in the growth cone stimulate axon extension (Gu and Spitzer, 1995) and Ca 2+ transients in the filopodia induce growth cone turning (Gomez et al, 2001). The downstream actions of Ca 2+ in neurons include control of growth cone traction (Conklin et al, 2005), polymerization of cytoskeletal structural elements (Lautermilch and Spitzer, 2000) and membrane insertion at growth cones (Lockerbie et al, 1991;Wood et al, 1992), which have direct effects on neurite outgrowth behaviour. By creating local increases in [Ca 2+ ] i at growth cones, the neurite can be steered (Henley and Poo, 2004).…”
Section: +mentioning
confidence: 99%